Larvae of the Costa Rican Hetaerina (Odonata: Calopterygidae) with comments on distribution - Zloty, Jacek (1993)
The larvae of seven of the nine Costa Rican species of Hetaerina (H.capitalis, H.cruentata, H. fuscogutfata, H. majuscula, H. miniata, H. occisa and H. titia) were identified by matching their Cellulose Acetate Gel Electrophoresis (CAGE) patterns with those of adults. CAGE allows larval descriptions to be processed at a much faster rate than through traditional rearing techniques and, provided that refrigeration and a power supply are available, is relatively portable and robust. Adults of H.capitalis, H.cruentata and H. miniata were also reared from final instar larvae. Larvae of H.caja and H.sempronia were identified by site association with adults and unique suites of morphological characters. Characters on the head, antennae, labium, pronotum, legs, abdomen, and caudal appendages are described and illustrated, and a key to final instar larvae of all nine species is presented. The distribution of Hetaerina in Costa Rica is influenced primarily by the Cordillera.